Um estudo sobre a (des)concentração industrial no Paraná na década de 90 - Simm, Eduardo Bolicenha (2003)
The present work sought to analyze the alterations in the location of the industry in Paraná during the ninth decade of the twentieth century. The work consisted on verifying whether there was concentration or spatial separation of the industrial activity for different industrial fields and for the Transformation Industry, as well as on pointing out the locations in which either of the processes occurred. This work also aimed to determine which industrial fields are more or less concentrated in the state. The analysis proposed was the building of maps containing the participation of each county in the added industrial value, according to specific fields as well as according to the total Transformation Industry. Data was used on a county level, incorporating the location of the county in the calculations. The analysis detected that the fields of Transportation, Wood, Paper and Cardboard presented a greater process of concentration; the fields of Non Metallic Minerals, Electrical Materials and Communications, and Chemicals have also undergone some concentration, however not as great as the former. The fields of Mechanical, Plastic Materials and Metal Industries underwent the greatest degree of spatial separation. In spite of this alteration, however, the Mechanical Industry remains one of the most concentrated activities in the state. The Furniture, Beverage, Textile, Food and Clothing industries have also undergone spatial separation, although by a smaller degree. Considering the alterations in the Transformation Industry as a whole, it presented a small degree of concentration, behavior which was largely influenced by the Chemical and Transportation industries.